2020
DOI: 10.1177/2325967120960206
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of American Football Injuries at Universities in the United Kingdom

Abstract: Background: College-level American football injury data are routinely collected; however, data relating to American football injuries at universities in the United Kingdom have never been reported. Purpose: To describe the epidemiology of UK university American football injuries. Study Design: Descriptive epidemiology study. Methods: An online survey tool was used to collect the injury data of 410 players from 56 UK university teams who participated in the 2014-2015 British Universities and College Sports Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…One potential risk of limited knowledge and experience of playing the game is increased injury incidence requiring medical intervention. Bayram et al (2020) have reported that UK university AF injuries to be comparably different to US collegiate football injuries. Specifically, UK university players were found to have a greater risk of concussion and more severe injuries.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…One potential risk of limited knowledge and experience of playing the game is increased injury incidence requiring medical intervention. Bayram et al (2020) have reported that UK university AF injuries to be comparably different to US collegiate football injuries. Specifically, UK university players were found to have a greater risk of concussion and more severe injuries.…”
Section: Introductionmentioning
confidence: 97%
“…Running backs and linebackers were found to have the highest injury rates, potentially due to their involvement in high-speed tackles (Edwards et al, 2018;Ward et al, 2018). Moreover, injury rates in offensive and defensive linemen were proportionally higher than US collegiate athletes (Badgeley et al, 2013;Dompier et al, 2015;Bayram et al, 2020). It is proposed that these findings are due to small roster sizes found in the UK game, meaning more game time for individuals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations